Estado do Conhecimento sobre as Concepções de Crianças e de Jovens Acerca das Relações Étnico-Raciais - Almeida, Ana Gabrielle Alves de (2022)
This research, of bibliographic character, sought to understand, through the State of Knowledge, how children and young people internalize and build their conceptions about ethnic-racial relations, since, from these ideas, one can, in addition to understanding how they are organized, to intervene in the perception of this social reality more effectively. The methodology used is characterized as quantitative and qualitative. Thus, the study carried out used the two approaches, quali and quanti, in a complementary way, supported in a bibliographic way by the State of Knowledge, in searches in the database of the Brazilian Digital Library of Theses and Dissertations (BDTD), considering the time frame from 2003 to 2021, of works that, in some way, investigated the representations, conceptions and/or ideas of children and young people about ethnic-racial relations. Data analysis took place through the organization promoted by Content Analysis. In view of this, 22 researches were selected, among theses and dissertations, which were read in full and described as to their objectives, methodology and main results, among which stand out, as results, the importance of systematically addressing ethnic relations in education. -racial in order to facilitate the deconstruction of the negative perception of black identity, through dialogues, as well as contact with references that value the black in art, history, culture, in short, in society as a subject of rights. The relevance of this study is given as it is possible to identify how the ethnic-racial relations are understood by children and young people, in Brazilian investigations, allowing to observe the evolution or not of these thoughts at different age moments. In addition, based on the results, reflections can be outlined for the school and society on the subject and the need to expand the discussions to deepen the theme and, thus, contribute to the fight against racist practices, still present in the current scenario of our social relationships.